Prevalence and Factors Associated with Anemia in Pregnancy among Women Receiving Antenatal Care at the West Gonja District Hospital of Northern Ghana - Danaah Malick, Martin Mumuni; Maalekuu, Aloysius; Rivera, Odalys Hernandez (International Journal of Innovative Research in Medical Science, 2020)
Background: Anemia in pregnancy is a major public health problem especially in Low and Middle-income countries (LMIC) including Ghana and is defined by the World Health Organization (WHO) as being present when the hemoglobin concentration in the peripheral blood is 11g/dl or less. In most African countries anemia in pregnancy occurs if the hemoglobin concentration falls below 10g/dl. Pregnant women are at a higher risk of developing anemia due to several factors such as hemodilution, nutritional factors, multiple gestation, socio-economic status and malaria infestation. Anemia in pregnancy is an important cause of maternal mortality and affects half of pregnant women worldwide; with 56% of West African pregnant women being anemic. The objective of this study is to assess the prevalence and identify the risk factors associated with anemia among pregnant women receiving antenatal care at the West Gonja Hospital(WGH) Methods: A cross-sectional was conducted with 136 pregnant women receiving antenatal care at the WGH between January 2017 to February 2018. Random sampling was used to select participants and data was collected using a structured questionnaire. Data was analyzed using the SPSS Version 24.0. Results: A total 71(52.2%) of the study population were anemic, while 65 (47.8%) were not anemic. 20(74.1%) of the 27 pregnant housewives were anemic, while 11(64.7%) of the pregnant farmers were anemic. 27 (96.4%) of the 28 pregnant women who took their iron/folate supplement only some few days were anemic. 12 (100%) of the 12 participants who took their iron/folate supplement a few times a week were anemic. 4 (80%) of the 5 participants who never took their iron/folate supplement were anemic. 21 (70%) of those who did not sleep under ITN were anemic. 33 (84.6%) of the 39 patients who were diagnosed with malaria were also anemic. 28 (87.5%) of the 32 participants who took only 2 meals a day were anemic. 27 (79.4%) of the 34 patients who took liver, beef, chicken and fish only twice weekly were anemic. 15 (88.2%) of the 17 patients who drank tea some days in a week were anemic. Conclusion: Although most of the pregnant women were adequately educated on the most relevant aspects of anemia in pregnancy, more than half of them were still anemic. Anemia was more prevalent among pregnant uneducated housewives with poor nutritional habits. All the pregnant sickle cell disease patients as well as those diagnosed with malaria were also anemic.